2016
DOI: 10.1002/star.201500254
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the physicochemical properties of modified starch‐based wood nanocomposites

Abstract: Bio-based nanocomposites were prepared from starch and soft wood with water as the solvent via a green route with great engineering aspects. Methyl methacrylate (MMA) modified starch, dimethyloldihydroxyethyleneurea (DMDHEU), wood flour, glycerol, and montmorillonite clay (MMT) were employed to prepare the wood starch nanocomposites (WSNC). Three different percentages of MMT were employed to prepare the starch composites and the properties of MMT modified starch composites were studied through limiting oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…This might be due to the agglomeration of clay at higher loading. Similar agglomeration was observed by Baishya and Maji 21 while examining the TEM micrograph of nanoclay-loaded wood/starch composite. TEM results suggested that MMT layers were delaminated and well dispersed in 5 phr MMT-loaded composites…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…This might be due to the agglomeration of clay at higher loading. Similar agglomeration was observed by Baishya and Maji 21 while examining the TEM micrograph of nanoclay-loaded wood/starch composite. TEM results suggested that MMT layers were delaminated and well dispersed in 5 phr MMT-loaded composites…”
Section: Resultssupporting
confidence: 83%
“…Effect of silicate nanoclays as in situ reinforcement to the polymer matrix has been widely studied. 21 Introduction of nanoclay into the polymeric composite increases the thermal stability along with other properties. 22 There is little information in the literature regarding the use of RH in PVC for making composite.…”
Section: Introductionmentioning
confidence: 99%
“…Baishya et al [ 54 ] used starch and coniferous wood as raw materials and water as a solvent to prepare biomass-based nanocomposites. To prepare wood starch nanocomposites, wood starch nanocomposites (WSNC) were prepared using methyl methacrylate (MMA)-modified starch, dimethyl dihydroxyethylurea (DMDHEU), wood flour, glycerol, and montmorillonite (MMT) as raw materials.…”
Section: Composite Biological Intumescent Flame Retardantmentioning
confidence: 99%